Emotional Expressions of 1 Year Old Children in a Psycholinguistic Study in Karawang, 2021 - Intan Ratna Wati; Teti Sobari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this article is to provide information and an overview of emotional expression of 1 year old children in psycholinguistic studies.Based on initial observations made on one-year-old children, the first research subject could not say 1 word, only laughing expressions in front of their parents. In the first year the child should have started to understand instructions and say one word, then in the second and third year, the child has started to recognize and learn to pronounce simple words even though the pronunciation is not so perfect.This type of research is qualitative research. The method used in this research is descriptive method.Psycholinguistics tries to describe the psychological processes that take place when a person pronounces the sentences he hears when communicating and how these language skills are acquired.The results of research conducted by researchers based on language acquisition data, researchers found that two respondents both could not pronounce 1 word. Either mama, papa, or other words that are usually spoken to children aged 1 year.